2007
DOI: 10.1016/j.jana.2007.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Audio Computer-Assisted Interviewing Software in HIV/AIDS Research

Abstract: Computer assisted interviewing (CAI) has begun to play a more prominent role in HIV/AIDS prevention research. Despite the increased popularity of CAI, particularly audio computer assisted self-interviewing (ACASI), some research teams are still reluctant to implement ACASI technology due to lack of familiarity with the practical issues related to using these software packages. The purpose of this paper is to describe the implementation of one particular ACASI software package, the Questionnaire Development Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 14 publications
(17 reference statements)
2
25
0
1
Order By: Relevance
“…Finally, data on risk behaviors, including self-reported drug use, have been captured through an ACASI software system, a standardized method for data collection that safeguards privacy and has been shown in numerous populations to increase the accurate and unbiased reporting of behaviors that may be socially sensitive. 7880 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, data on risk behaviors, including self-reported drug use, have been captured through an ACASI software system, a standardized method for data collection that safeguards privacy and has been shown in numerous populations to increase the accurate and unbiased reporting of behaviors that may be socially sensitive. 7880 …”
Section: Discussionmentioning
confidence: 99%
“…Second, we may have underestimated the prevalence of these behaviors in some groups using interviewer-administered questionnaires due to socially desirable reporting. We will consider using audio computer-assisted self-interviewing (ACASI) for future studies, which has been shown to capture risk reporting more accurately (Pluhar et al 2007;Simoes et al 2006) and can be used in low literacy populations (NIMH Collaborative HIV/STD Prevention Trial Group 2007). Finally, our results may not be generalizable to all IDU, FSW or MSM populations in Spain as their experience with HIV testing, prevention, and research may differ with regard to factors that could affect willingness to participate in future vaccine trials (Buchbinder et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…All data were collected utilizing an audio computer-assisted selfinterview (ACASI) program. 14,15 Further methodological detail about this trial has been previously published. 16 The current study consists of data collected at the baseline assessment, prior to treatment group randomization.…”
Section: Methodsmentioning
confidence: 99%